Colombia : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Colombia. (IMF Staff Country Reports; Country Report, 2022)
Colombia's economy rebounded strongly in 2021 with 10.6 percent growth led by pent-up domestic demand, notably private consumption. Around 66 percent of the population is fully vaccinated against Covid-19 as of end-February and the economy continues to reopen more fully. While GDP has already reached pre-pandemic levels, employment has trailed in its recovery and macroeconomic imbalances have emerged. Amid strong demand, supply constraints, and rising commodity prices, rising inflation exceeded the upper limit of the central bank's tolerance range in 2021. With demand-led growth and higher import prices, the current account deficit widened to 5 3/4 percent of GDP. Under staff's assumptions for the evolution of the pandemic, above-potential growth around 5 1/2 percent is expected in 2022, led by robust household consumption and a continued recovery of investment and exports. External vulnerabilities remain elevated with high external financing needs and tighter financial conditions. External risks remain elevated and an intensification of the ongoing conflict in Ukraine may impart considerable volatility in financial and commodity markets. Domestic risks are also tilted to the downside-including uncertainty around the evolution of the pandemic, political uncertainty with national elections this year, and slower implementation of the infrastructure agenda and peace accords.